Safety, Tolerability, and Pharmacokinetics of PF‐06823859, an Anti–Interferon β Monoclonal Antibody: A Randomized, Phase I, Single‐ and Multiple‐Ascending‐Dose Study. Issue 3 (22nd December 2020) - Neelakantan, Srividya; Oemar, Barry; Johnson, Kristen; Rath, Natalie; Salganik, Mikhail; Berman, Gabe; Pelletier, Kathleen; Cox, Lori; Page, Karen; Messing, Dean; Tarabar, Sanela
Abstract: This double‐blind, randomized, placebo‐controlled, dose‐ascending, first‐in‐human study (NCT02766621) assessed the safety, tolerability, and pharmacokinetics (PK) of PF‐06823859, an anti–interferon β monoclonal antibody. Healthy subjects were randomized to single ascending doses (SADs) of intravenous PF‐06823859 30, 100, 300, 900, or 2000 mg or placebo; to multiple ascending doses (MADs) of subcutaneous PF‐06823859 100 or 300 mg or placebo (once every 2 weeks for a total of 3 doses); or to MAD of intravenous PF‐06823859 600 mg or placebo (once every 3 weeks or once every 4 weeks for a total of 2 doses). The incidence, severity, and causal relationship of adverse events (AEs) were assessed, along with immunogenicity and PK. In total, 62 subjects were randomized to treatment (SAD, n = 35; MAD, n = 27). There were 76 treatment‐emergent all‐causality AEs in the SAD (PF‐06823859: n = 25; placebo: n = 4) and MAD (PF‐06823859: n = 40; placebo: n = 7) cohorts. In the SAD cohorts, all treatment‐emergent all‐causality AEs were mild in severity; 4 AEs of moderate severity were identified in the MAD cohorts. No dose‐limiting AEs, serious AEs, treatment‐related discontinuations, dose reductions, or deaths occurred. PF‐06823859 exposure increased dose‐proportionally, with half‐life values ranging between 23 and 35 days. The estimated subcutaneous bioavailability was 43% to 44%. Immunogenicity incidence rates were low (antidrug antibodies, 12.5%; neutralizing antibodies, 2.1%). No immunogenically related clinical responses of concern were observed. In conclusion, PF‐06823859 demonstrated an acceptable safety, tolerability, and PK profile that supports clinical development for treating disorders associated with increased interferon β levels, such as dermatomyositis or systemic lupus erythematosus.